Alcohol and Alkane Organic Extraction Using Pervaporation Process - Hamouni, Samia; Arous, Omar; Abdessemed, Djamel; Nezzal, Ghania; Van der Bruggen, Bart (Macromolecular symposia., 2019)
In this work, different feed mixtures are investigated for the separation of alcohol‐water, toluene‐water, alcohol‐toluene, and alkane‐toluene mixtures by pervaporation using a poly (dimethylsiloxane) membrane (PDMS). The polymeric membrane is characterized by Fourier transform infrared spectrometry (FTIR), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). The total flux and membrane selectivity for hexane‐toluene mixtures are found to be greater than those obtained for heptane‐toluene, alcohol‐toluene, toluene‐water, and alcohol‐water mixtures. Moreover, the total flux and selectivity for the alkane‐toluene mixtures are found to be higher than those obtained for the alcohol‐toluene mixtures. The feed concentration and the temperature for hexane‐toluene mixture have the same effect on the membrane total flux. Overall, the pervaporation separation index (PSI) decreases with increasing feed concentration. The highest PSI value of 20 359 g m−2 h−1 is found at a hexane feed concentration of 10 wt%, a temperature of 40 °C, a permeation flux equal to 717 g m−2 h and a selectivity of 29.